Sufism of Ahl al-Sunnah wa al-Jama‘ah (ASWAJA) Scholars of the Nusantara: A Comparative Study of the Thought of Shaykh Arsyad al-Banjari, Shaykh Nawawi al-Bantani, and Kiai Haji Hasyim Asy‘ari - Muhammad Noor Alamsyah; Khalilurrahman; M. Anshari (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
Sufism holds a strategic position in shaping the Islamic character of the Nusantara community one that is moderate, tolerant, and civil. This article provides a comparative study of the thoughts of three prominent Nusantara scholars: Syekh Arsyad al-Banjari, Syekh Nawawi al-Bantani, and KH. Hasyim Asy’ari within the framework of Ahlussunnah wal Jama‘ah (Aswaja). The study employs a literature-based approach by examining primary works as well as relevant secondary sources. The findings reveal that all three scholars regard Sufism as a dimension that perfects the Sharia, characterized by an ethical-moral orientation (tasawwuf akhlaqi) that emphasizes purification of the soul, cultivation of proper conduct, and integration of Sharia, ethics, and spiritual practice. Syekh Arsyad al-Banjari highlights soul purification grounded in adherence to Sharia; Syekh Nawawi al-Bantani stresses a Sufism centered on ihsani ethics and social responsibility; while KH. Hasyim Asy’ari positions Sufism as the moral foundation of santri education, especially within pesantren traditions. Comparatively, the three scholars share a convergent orientation toward religious moderation, rejection of extreme forms of Sufism, and reinforcement of social ethics. Their ideas remain highly relevant in addressing contemporary challenges such as moral degradation, digital disruption, radicalism, and mental health issues. Thus, the Sufi legacy of Nusantara scholars within the Aswaja perspective carries not only historical value but also serves as a transformative paradigm for modern Islamic spirituality and education.